The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0159883
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Spatial Variation in Acoustic Environments Using Sound Mapping

Abstract: Animals select and use habitats based on environmental features relevant to their ecology and behavior. For animals that use acoustic communication, the sound environment itself may be a critical feature, yet acoustic characteristics are not commonly measured when describing habitats and as a result, how habitats vary acoustically over space and time is poorly known. Such considerations are timely, given worldwide increases in anthropogenic noise combined with rapidly accumulating evidence that noise hampers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…While we observed that traffic noise was a dominate component at many of our recording locations, other foreground and background sources were also present. As demonstrated by Job et al (2016), urban acoustic environments can be highly variable at small scales (i.e. street scales), although global trends have also been found on large scales (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While we observed that traffic noise was a dominate component at many of our recording locations, other foreground and background sources were also present. As demonstrated by Job et al (2016), urban acoustic environments can be highly variable at small scales (i.e. street scales), although global trends have also been found on large scales (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Future work on this application with SPreAD-GIS might benefit from altering the tool to place less importance on the wind factor (and adjust other factors as necessary). Future work might consider ground-truthing sound estimates during monthly siren tests using in situ microphone arrays similar to Job et al (2016). This would confirm or refute the importance of wind (and other factors), which in this example was highly significant, on the sound propagation estimates.…”
Section: Discussionmentioning
confidence: 82%
“…While this type of approach is efficient, it is not without its limits. Ultimately, the analysis is constrained by the fact that buffers are based on ideal, theoretical estimates of the distance from the siren that the siren noise will reach; these types of estimates do not factor in the intricacies of sound propagation (Webster, 2014) and the role of environmental factors such as topography, weather conditions (e.g., temperature, wind, humidity), and land cover (Job et al, 2016). Such factors influence citizens' ability to hear the sirens; e.g., Hodler (1982) observed that sirens were inaudible to Kalamazoo residents located upwind.…”
Section: Gis-based Extent and Coverage Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, environmental features can affect the propagation and intensity of light and noise exposure. For instance, a study that mapped sound propagation from playbacks in three terrestrial habitats found forests had broader sound pressure level gradients than prairie or urban habitats due to more sound reflection and reverberation (Job et al, 2016). Seasonally changing environmental conditions could also alter an organism's response to sensory stimuli.…”
Section: Introductionmentioning
confidence: 99%